RANCANG BANGUN SISTEM INFORMASI E-TRACE ALUMNI DI SMKN 1 PRAYA TENGAH - Ahmad tantoni; Lalu Rajiv Riyan Kurniawan; Maemun Saleh (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2022)
Special Job Fair (SJF) of Vocational High School 1 Central Praya is distress to trace alumni data in every year, especially in 2019. Therefore need a Information System of alumni tracing data that easier to SJF work effectivelly and efficienlly. This research is using SDLC development method, SWOT analysis method, observation, interview, questionnaire and document data collection method and black box testing method. This Information System Alumni E-Trace Data has many interesting features like online disccussion forum, donation and frequently Asked Question (FAQ). This Information System Alumni E-Trace Data is working well and corresponding by design. No errors found so far. The features is working well too and tested by Black Box testing. Special Job Fair (SJF) of Vocational High School 1 Central Praya should be learn more to operate the Information System Alumni E-Trace Data and do socialization about this Information System to related party.